THE SMALLNESS OF SMALL STATES: BETWEEN POWER AND VULNERABILITY - Happy Tracy Stephanie (Jurnal Studi Diplomasi dan Keamanan, 2018)
This essay examines the power of small states in global development diplomacy. This essay seeks to address the following things. The power and obstacles of small states in global development diplomacy, how small states can increase their power, and the limitations of small state diplomacy. The most important part of this essay is the analysis related to the strategies to increase the power of small states. This essay argues that the sources of power of small states in global development diplomacy are the rise of non-traditional issues and their inherent resilience. Moreover, small states can use strategies of coalition building, issue prioritisation, and agenda setting to increase their power in global negotiations through intergovernmental organisations, focusing on the United Nations.